2019
DOI: 10.1111/liv.14081
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in presentation and outcomes of paediatric autoimmune hepatitis

Abstract: Background & Aims Most studies on autoimmune hepatitis (AIH) in children are in predominantly Caucasian cohorts. Paediatric AIH in African Americans (AA) is understudied, with a dearth of clinical predictors of outcome, often leading to serious complications and even mortality. The aim of the study was to define disease presentation, progression, response to therapy and outcomes in paediatric AIH in a well‐defined, large, single centre, demographically diverse population. Methods We conducted a review of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
1
12
0
5
Order By: Relevance
“…Alaskan Natives have a high frequency of icteric AIH at presentation, Hispanics more commonly present with cirrhosis, and African Americans have accelerated progression of disease and a higher rate of recurrence after LT compared to other races. (5,6) Female predominance occurs in adults (71%-95% women) (7)(8)(9)(10)(11)(12) and children (60%-76% girls). (13)(14)(15)(16) Early epidemiological reports suggested that the onset of AIH had age peaks at 10-30 and 40-60 years, but the findings may have been influenced by referral bias.…”
Section: Background Epidemiologymentioning
confidence: 99%
“…Alaskan Natives have a high frequency of icteric AIH at presentation, Hispanics more commonly present with cirrhosis, and African Americans have accelerated progression of disease and a higher rate of recurrence after LT compared to other races. (5,6) Female predominance occurs in adults (71%-95% women) (7)(8)(9)(10)(11)(12) and children (60%-76% girls). (13)(14)(15)(16) Early epidemiological reports suggested that the onset of AIH had age peaks at 10-30 and 40-60 years, but the findings may have been influenced by referral bias.…”
Section: Background Epidemiologymentioning
confidence: 99%
“…As we all know, GGT is positively correlated with the severity of liver disease. Palle et al had demonstrated that more AIH in African Americans presented with end-stage liver disease (ESLD) with high GGT [29]. Recently, lipid metabolism has been found to play an important role in the developmental differentiation and typing of various immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…9 Esto coincide con los hallazgos encontrados por Porta et al en la mayor cohorte de pacientes reportada en Brasil (y también para toda Latinoamérica), con una muestra de 828 pacientes, donde el 89,6% se clasificaron como HAI tipo I y fue predominante en el sexo femenino. 10 Vale la pena destacar que estos hallazgos no son solo equiparables a los datos presentados en cohortes latinoamericanas, sino que también coinciden con lo reportado en la literatura mundial, como se evidencia en la serie más grande de pacientes asiáticos con HAI descrita por Lee Way et al, donde un 59% de los pacientes correspondían al sexo femenino y la mayoría se presentaron como HAI tipo I, en un 56%. 11 Sin embargo, dicho porcentaje es significativamente menor que los descritos anteriormente.…”
Section: Figura 2 Niveles De Ast Y Alt Iniciales Y Postratamientounclassified
“…9 En un estudio reciente de HAI se mostró un mayor riesgo de trasplante temprano y recurrencia postrasplante en pacientes pediátricos afroamericanos. 10 La población colombiana desciende principalmente de tres grupos raciales (amerindios, europeos y africanos), lo que da lugar a una considerable diversidad genética. 11 Se han realizado estudios previos de HAI en México, Brasil y Argentina, que muestran resultados similares a reportes internacionales anteriores, evidenciando una mayor prevalencia de HAI tipo I y predominio en el sexo femenino.…”
Section: Introductionunclassified
See 1 more Smart Citation